The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3311/ppci.14177
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Comparison between Spiral Transverse RC and CFST Columns under Loads of Varying Eccentricities

Abstract: This paper is the first to present the results of a numerical comparison between the performances of two newly developed concrete columns namely: multi-tied spiral transverse reinforced (MTSTR) column and concrete-filled steel tube (CFST) column under eccentric compressive loads. The behavior of MTSTR columns under eccentric loads has not been studied until today and also this behavior is not compared to that of the CFST columns. The numerical models of these columns were constructed using the nonlinear finite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…The plasticity input parameters, compressive, and tensile behavior input parameters used in the CDP model are outlined in Tables 1-3, respectively [27][28][29][30][31]. The plastic parameters in Table 1 are the optimized parameters and they are selected based on the previous studies of the author [16,27,28]. Several tries for dilation angle was selected between 5° to 55° and the optimized value was obtained as 30°.…”
Section: Numerical Model Development and Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasticity input parameters, compressive, and tensile behavior input parameters used in the CDP model are outlined in Tables 1-3, respectively [27][28][29][30][31]. The plastic parameters in Table 1 are the optimized parameters and they are selected based on the previous studies of the author [16,27,28]. Several tries for dilation angle was selected between 5° to 55° and the optimized value was obtained as 30°.…”
Section: Numerical Model Development and Verificationmentioning
confidence: 99%
“…The test results obtained by Nie et al showed that CPSW systems connected by shear studs have adequate ductility. Labibzadeh et al [16] Obtained good results by comparing the performance of two newly developed concrete columns MTSTR and CFST under eccentric compressive loads. In this modeling, nonlinear finite element method is used.…”
Section: Introductionmentioning
confidence: 99%
“…The most common steel-concrete composite member is the concrete filled steel tube (CFST) column. The structural performance of CFST members has been the subject of numerous experimental and analytical research [3][4][5]. Relevant design specifications have been established in various nations and areas as a result of these findings to better guide the design of CFST members and structures.…”
Section: Introductionmentioning
confidence: 99%
“…Residual damages occur depending on the magnitude of the earthquake in reinforced concrete structures exposed to earthquake loads. Experimental and analytical studies have been carried out by many researchers to identify these damages [1][2][3]. Lehmann et al [4] suggest that key damage states of residual cracking, cover spalling, and core crushing can best be related to engineering parameters, such as longitudinal reinforcement tensile strain and concrete compressive strain, using cumulative probability curves.…”
Section: Introductionmentioning
confidence: 99%